Adsorption of Hazardous Azorhodanine Dye from an Aqueous Solution Using Rice Straw Fly Ash. Issue 5 (3rd May 2016) - El-Sonbati, A. Z.; El-Deen, I. M.; El-Bindary, M. A.
Abstract : The potential of using rice straw fly ash (RSFA) as low-cost adsorbents for the removal of hazardous azorhodanine (AR) dye from aqueous solution was investigated. The effects of different variables in the batch method as a function of solution pH, contact time, concentration of adsorbate, adsorbent dosage, and temperature were investigated, and optimal experimental conditions were ascertained: 0.05 g for initial dye concentration of 20–100 mg/L at pH 2. The experimental equilibrium data were tested by the isotherm models, namely the Langmuir and Freundlich adsorption and the isotherm constants were determined. The kinetic models, pseudo-first-order and pseudo-second-order, were employed to analyze the kinetic data. The activation energy of adsorption was also evaluated and found to be +10.89 kJ.mol −1, indicating that the adsorption is physisorption. Various thermodynamic parameters, such as Gibbs free energy, entropy, and enthalpy of the ongoing adsorption process, have been calculated and found to be spontaneous and exothermic, respectively. GRAPHICAL ABSTRACT: